Electronic transparency of internal interfaces in metallic nanostructures comprising light, heavy and ferromagnetic metals measured by terahertz spectroscopy - Beermann Nicolas S.; Fabretti Savio; Hafez Hassan A.; Syskaki Maria-Andromachi; Kononenko Iryna; Jakob Gerhard; Kläui Mathias; Turchinovich Dmitry (Nanophotonics)
We investigate the electronic transport at the internal interface within a selection of metallic bilayer nanostructures using the contact-free, all-optical method of THz time-domain spectroscopy. The Ru/Co, Ru/Pt, and Ru/Al bilayer nanostructures and their individual constituent metals are studied, with Ru representing an archetypal d-band metal, Co an archetypal ferromagnet, and Pt and Al archetypal heavy and light metals, respectively. The THz conductivity data were analyzed in terms of Drude and Bloch–Grüneisen models, and the interface current coefficient of the internal nanointerface was determined. Strong temperature dependency of the interface current coefficient in the Ru/Co nanostructure is revealed.